Analyzing of Students Lack in English for Specific Purposes Students of Senior High School 16 Makassar - Rahmat Lilaalamin, Dzulqarnain; Rahmat, Subhan (RITMA: Journal of Islamic Integrated Research, Science, and Community, 2024)
This study aims to provide information about the lack or obstacles in the teaching and learning of students of SMAN 16 Makassar towards English. Therefore, a lack analysis is needed to find out what are the obstacles to students in teaching and learning English. This research was conducted to collect information about the problems of English in order to analyse what are the obstacles or lack experienced by students in English language learning. In this study, researchers used quantitative methods with a questionnaire through Google form as a research instrument. The respondents of this study were the students of SMAN 16 Makassar with a total of 54 students who were divided into 2 groups, which were class X-j totaling 24 students, and class XI IPS 4 totaling 30 students. The results found after conducting this research are that, the students of SMAN 16 Makassar experience several obstacles and shortcomings during English learning, such as embarrassing or nervous in implementing dialog to their friends, they also experience a lack of practice in speaking skills in English, and so on.